2022
DOI: 10.1101/2022.04.04.487015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Point mutations in the catalytic domain disrupt cellulose synthase (CESA6) vesicle trafficking and protein dynamics

Abstract: Cellulose, as the main component of the plant cell wall, is synthesized by a multimeric protein complex named the cellulose synthase (CESA) complex or CSC. In plant cells, CSCs are transported through the endomembrane system to the PM, but how catalytic activity or conserved motifs around the catalytic core domain influence vesicle trafficking or protein dynamics is not well understood. Here, we used a functional YFP-tagged AtCESA6 and site-directed mutagenesis to create 18 single amino acid replacement mutant… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…We also found that after photobleaching, YFP-CESA6 particles with an atypical pause phase of over 110 sec were almost 50% more abundant in prc1-1 trs85-1 than prc1-1 (Figure 4d). CESA6 particles that remain static at the plasma membrane have also been reported in exocytosis mutants (Zhu et al, 2018), endocytotic mutants (Bashline et al, 2015) and transgenic lines that have point mutations in the catalytic domain of YFP-CESA6 (Huang, 2022). These static particles likely represent unsuccessful insertion events, delayed endocytotic events, or the insertion of functionally inactive CSCs.…”
Section: Cme Is Reduced In Trs85-1mentioning
confidence: 82%
“…We also found that after photobleaching, YFP-CESA6 particles with an atypical pause phase of over 110 sec were almost 50% more abundant in prc1-1 trs85-1 than prc1-1 (Figure 4d). CESA6 particles that remain static at the plasma membrane have also been reported in exocytosis mutants (Zhu et al, 2018), endocytotic mutants (Bashline et al, 2015) and transgenic lines that have point mutations in the catalytic domain of YFP-CESA6 (Huang, 2022). These static particles likely represent unsuccessful insertion events, delayed endocytotic events, or the insertion of functionally inactive CSCs.…”
Section: Cme Is Reduced In Trs85-1mentioning
confidence: 82%
“…The inability of PlPeL8 mutants to induce cell death might stem from the crucial roles of New Phytologist certain residues in mediating protein interactions, dimer formation, structure alterations, or folding modifications. A recent study has revealed the involvement of several aspartic acid residues within the catalytic domain of cellulose synthase CESA6 involved in complex formation, protein folding, and dynamics (Huang et al, 2023). Additionally, amino acids at positions C18 and C44 are crucial for Botrytis HR-inducing protein 1 (Hip1)induced cell death and might be associated with native conformation (Jeblick et al, 2023).…”
Section: Discussionmentioning
confidence: 99%